Mortality of olive ridley turtles Lepidochelys olivacea due to incidental capture in fishing nets along the Orissa coast, India - Pandav, B.; Choudhury, B. C.; Kar, C. S. (Oryx, 1997)
The coastal state of Orissa, India, harbours three important mass-nesting beaches of the olive ridley sea turtle Lepidochelys olivacea. During a survey of sea turtle nesting beaches from December 1993 to May 1994, 5282 dead olive ridleys were counted along the 480 km coastline of Orissa. Almost all the deaths were due to incidental capture in offshore fishing nets. Increased fishing activities in the coastal waters near important sea-turtle nesting beaches pose a serious threat to the survival of this endangered sea turtle. It is therefore suggested that coastal waters adjacent to major sea-turtle nesting beaches be declared as closed areas for commercial fishing activities in order to ensure the sea turtle's long-term survival.